Distinct Responses of Elasmobranchs and Ray-Finned Fishes to Long-Term Global Change - Guinot, Guillaume; Cavin, Lionel (Frontiers in Ecology and Evolution, 2020)
Both biotic and abiotic factors likely played a role in influencing the diversification patterns of clades. Although the role of environmental forcing on the long-term evolution of biodiversity has been explored for invertebrate clades, little is known about how vertebrates groups responded to environmental changes. Among vertebrates, fishes (ray-finned fishes and elasmobranchs) have a long, rich and complex evolutionary history comprising numerous diversification and extinction events. Yet, knowledge on the causes for the diversity fluctuations of these most speciose aquatic vertebrate clades in modern marine and continental ecosystems were restricted to qualitative interpretations. Here we use multiple regression methods to quantitatively examine the role of six abiotic parameters over the long-term variations of elasmobranch and actinopterygian genus-level diversity. We find that marine actinopterygian diversity is mainly controlled by temperature while continental fragmentation is the primary driver of the diversity fluctuations of elasmobranchs. Sea-level variations correlate positively with the diversity variations of both marine groups, whereas none of the tested proxies explains the diversity variation of freshwater ray-finned fishes. Our results indicate that such contrasting responses are mainly due to ecological and life-history trait differences between these groups.